Chapter 2: Beyond Process: The Material Framework for Detention and the Particularities of Non-International Armed Conflict. (2nd February 2015) - Mahnad, Ramin
Abstract: Deprivation of liberty in non-international armed conflict (NIAC) has suffered no shortage of attention over the last decade with issues surrounding the legal basis and procedural requirements for detention having received the most focused attention. In the course of these debates, international lawyers have looked to rules found in international humanitarian law (IHL) applicable in international armed conflict (IAC) for guidance, and many have argued that as a matter of either law or policy, the procedural aspects of detention in NIAC should be approached in a similar manner. As these discussions have evolved, their focus on grounds and procedure has left another core aspect of IHL relatively unnoticed, along with its potential role in the evolution of NIAC detention law and policy: in addition to providing a procedural framework for detention in armed conflict, IHL also provides material framework for detention that addresses the physical conditions in which detainees are to be held and the way detention and detention facilities are managed. It is often overlooked that in IAC, IHL's accounting for the unique situation of armed conflict does not stop at the right to detain or the grounds and procedures for doing so, but also informs extensive rules on the material aspects of detention. The result is a series of essential and unique protections—often going beyond those found in human rights law—designed to address specific vulnerabilities caused by armed conflict. This article calls attention to this aspect of IHL and asks whether the logic and reasoning that informs the material framework for detention established by the Geneva Conventions should have a role to play in the evolution of law and policy governing the material framework for detention in NIAC.